Reviews on Corrosion Inhibitors: A Short View - Raja, P.; Ismail, Mohamed; Ghoreishiamiri, S.; Mirza, J.; Ismail, M.; Kakooei, S.; Rahim, A. (Taylor and Francis Inc, 2016)
A range of numerous corrosion inhibitors, viz. organic molecules with hetero atoms and p-electron clouds, inorganic salts and plant excerpts likewise their corresponding phytoconstituents were reported with success for metals in different corrosive media. Various literature reviews related to corrosion inhibitors have been reported by many authors based on their application, classification, and inhibition mechanism. A short view of all these reviews is summarized in this manuscript. Various aspects of corrosion inhibitors as well as their recent trends and advancement are also discussed.